A novel online fluorescence method for in-vivo measurement of hydrogen peroxide during oxidative stress produced in a temporal lobe epilepsy model. Issue 8 (23rd May 2018) - Pardo-Peña, Kenia; Sánchez-Lira, Ana; Salazar-Sánchez, Juan C.; Morales-Villagrán, Alberto
Abstract : Status epilepticus (SE) can result in an overproduction of hydrogen peroxide (H2 O2 ), which contributes to oxidative stress and brain injury during different phases of epileptogenesis and seizures. In this study, we measured the extracellular H2 O2 concentration in the rat hippocampus in a temporal lobe epilepsy model. A new fluorescent technique for measuring H2 O2 in vivo simultaneously with electroencephalography recording was tested. The method consists of mixing microdialysate with an enzymatic reactor to produce a fluorescent compound. The fluorescence intensity was measured every second and was proportional to the H2 O2 concentration. The results showed that H2 O2 was released during SE; we detected a significant increase of up to five times over the baseline value that correlated with changes in electrical activity. We also observed that H2 O2 was produced for days after SE and was associated with continuous neuronal death and seizure generation. Therefore, we monitored H2 O2 48 h and 15 days after SE, observing increases of up to 96 and 124%, respectively, accompanied by changes in electrical activity with spontaneous discharges of large amplitude. These changes may reflect the oxidative stress generated during epileptogenesis that remains during the chronic period (458% increased) with the presence of large spikes, indicating that the H2 O2 could also participate in the generation and maintenance of spontaneous recurrent seizures. There are no previous reports on the detection of H2 O2 at this temporal resolution; thus, this study contributes a novel technique for studying and understanding epileptogenesis to develop new antioxidant strategies for the treatment of temporal lobe epilepsy.